Teach-back of discharge instructions in the emergency department: a pre–post pilot evaluation. Issue 2 (17th June 2021) - Hesselink, Gijs; Sir, Özcan; Koster, Nadia; Tolsma, Carolien; Munsterman, Maartje; Olde Rikkert, Marcel; Schoon, Yvonne
Abstract : Objectives: With the 'teach-back' method, patients or carers repeat back what they understand, so that professionals can confirm comprehension and correct misunderstandings. The effectiveness of teach-back has been underexamined, particularly for older patients discharged from the emergency department (ED). We aimed to determine whether teach-back would reduce ED revisits and whether it would increase patients' retention of discharge instructions, improve self-management at home and increase satisfaction with the provision of instructions. Methods: A nonrandomised pre–post pilot evaluation in the ED of one Dutch academic hospital including patients discharged from the ED receiving standard discharge care (pre) and teach-back (post). Primary outcomes were ED-revisits within 7 days and within 8–30 days postdischarge. Secondary outcomes for a subsample of older adults were retention of instructions, self-management 72 hours after discharge and satisfaction with the provision of discharge instructions. Results: A total of 648 patients were included, 154 were older adults. ED revisits within 7 days and within 8–30 days were lower in the teach-back group compared with those receiving standard discharge care: adjusted odds ratios (AORs) of 0.23 (95% CI 0.05 to 1.07) and 0.42 (95% CI 0.14 to 1.33), respectively. Participants in the teach-back group had an increased likelihood of full knowledge retention on information related to their ED diagnosis and treatment (AOR 2.19; 95% CI 1.01 to 4.75; p=0.048), medication (AOR 14.89; 95% CI 4.12 to 53.85; p>0.001) and follow-up appointments (AOR 3.86; 95% CI 1.33 to 10.19; p=0.012). Use of teach-back was not significantly associated with improved self-management and higher satisfaction with discharge instructions. Discharge conversations were generally shorter for participants receiving teach-back. Conclusions: Discharging patients from the ED with a relatively simple and feasible teach-back method can contribute to safer and better transitional care from the ED to home.